Associations of polygenic risk scores for preeclampsia and blood pressure with hypertensive disorders of pregnancy - Nurkkala Jouko; Kauko Anni; Finngen; Laivuori Hannele; Saarela Tanja; Tyrmi Jaakko S; Vaura Felix; Cheng Susan; Bello Natalie A.; Aittokallio Jenni; Niiranen Teemu (Lippincott Williams and Wilkins, 2025)
Background:
Preexisting hypertension increases risk for preeclampsia. We examined whether a generic blood pressure polygenic risk score (BP-PRS), compared with a preeclampsia-specific polygenic risk score (PE-PRS), could better predict hypertensive disorders of pregnancy.
Methods:
Our study sample included 141 298 genotyped FinnGen study participants with at least one childbirth and followed from 1969 to 2021. We calculated PRSs for SBP and preeclampsia using summary statistics for greater than 1.1 million single nucleotide polymorphisms.
Results:
We observed 8488 cases of gestational hypertension (GHT) and 6643 cases of preeclampsia. BP-PRS was associated with GHT [multivariable-adjusted hazard ratio for 1SD increase in PRS (hazard ratio 1.38; 95% CI 1.35–1.41)] and preeclampsia (1.26, 1.23–1.29), respectively. The PE-PRS was also associated with GHT (1.16; 1.14–1.19) and preeclampsia (1.21, 1.18–1.24), but with statistically more modest magnitudes of effect (P = 0.01). The model c-statistic for preeclampsia improved when PE-PRS was added to clinical risk factors (P = 4.6 × 10–15). Additional increment in the c-statistic was observed when BP-PRS was added to a model already including both clinical risk factors and PE-PRS (P = 1.1 × 10–14).
Conclusion:
BP-PRS is strongly associated with hypertensive disorders of pregnancy. Our current observations suggest that the BP-PRS could capture the genetic architecture of preeclampsia better than the current PE-PRSs. These findings also emphasize the common pathways in the development of all BP disorders. The clinical utility of a BP-PRS for preeclampsia prediction warrants further investigation.